EFQMQual: evaluating the implementation of the European quality award based on the concepts of model of service quality gaps and ServQual approach. Issue 3 (12th August 2014) - Shahin, Arash; Balouei Jamkhaneh, Hadi; Zahra Hosseini Cheryani, Sayedeh
Abstract : Purpose: – The major aim of this investigation is to propose a novel approach for evaluating the implementation of the European Quality Award, i.e. the model of European Foundation for Quality Management (EFQM). Design/methodology/approach: – The EFQM model includes both enablers and results, while in the service quality gaps model, only the gaps between the organization and customer are studied. In this paper, a new approach has been proposed to assess seven determined gaps in implementing the EFQM model based on the concepts of the service quality gaps model and the ServQual approach. The new approach to the EFQMQual has been examined in Isfahan Province Gas Company using different viewpoints of senior and middle managers and senior experts on four elements of determined gaps. These include perceptions of goals, expectations of goals, perceptions of assessment and expectations of assessment. Findings: – Findings indicate that leadership and key results criteria have the lowest and the highest gap values, respectively. In addition, the fifth gap, i.e. the difference between expectations of assessment and perceptions of assessment, has the lowest average, while the seventh gap, i.e. elements of the EFQM model, has the highest average. With regard to the correlation among the seven gaps, it became obvious that there is a significant correlation among the first, fifth and sixth gaps; and also between the fourth and fifth gaps. Finally, based on the Pareto rule, the priority of the criteria related to each of the gaps has also been determined. Research limitations/implications: – One of the limitations of this study is the complexity of the concepts in the questionnaires, which makes it difficult for respondents to understand the items of the questionnaires. To overcome this, therefore, the researcher has attached a guideline to the distributed questionnaires. Originality/value: – As the literature review indicates, there has not been any research on integrating the concepts of the service quality gaps model, the ServQual approach, and the EFQM model, while also analyzing the weak and strong results obtained from implementing the EFQM model based on such an integrated approach. The significance of the study lies further in the fact that based on an approach similar to the proposed EFQMQual, such concepts can be applied for evaluating the implementation of other quality award systems.